Relationship Between the Level of Knowledge of Nurses About Triage with The Application of Triage at Emergency Department Hospital - Rosario de J. Leite, Ana do; dos Santos, Julito; Noronha, Herminio; de Jesus Amaral, Isabel; Oqui, Maximiano; Francisca Simões, Laura (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: In the globalized world, it is important to be used triage system in emergency department so that you can classify the patient with triage categories according to the value of trauma or illness to start service quickly. Objective: This research was carried out to identify the level of knowledge of nursing about triage, the application of triage also to know the relationship between the level of knowledge of nurse about triage and application of triage in the emergency department of Hospital Nacional Guido Valadares Dili Timor-Leste. Method: the research of methodology the researcher uses the quantitative type with a cross sectional approach and a correlational study. Result and Discussion: through the research to identify 40 nurses in emergency department of Hospital Nacional Guido Valadares Dili Timor-Leste. The research identifies that the existing sample of 40 for variable level of knowledge, show that many had good knowledge with respondent 30 (75.0%) and respondent 2 (5.0%) with low knowledge and about the variable of triage implementation showed that many nurses agreed with the application of triage with 27 respondents (67.5%) and not in agreement with the application of triage with 3 respondents (7.5%). Based on the results of the study, it shows that there is a positive relationship between the level of knowledge and the application of triage with a value of r = 0.463 and a p value of 0.003 which is higher than the alpha value (0,05) meaning that Ho rejects Ha accept. Conclusion: This study shows that there is a relationship between the level of knowledge of nurses about triage and the application of triage at emergency department of Hospital Nacional Guido Valadares Dili Timor-Leste with a significant value of 0,003 < a = 0,05